Rizoma urbano, articulador de la ciudad (2020)
Urban Rizome is a project that seeks to articulate, revitalize and enhance the existing public space of the Santa Fe neighborhood in the city of Bogotá. The project is located in the lands on the south side of the Renacimiento Park, thus turning the project into an equipment for this great green heart that the sector has, which, at present, has a high level of deterioration due to the lack of ownership from the people of the sector.